2006
DOI: 10.1002/j.2055-2335.2006.tb00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems with Medication Use in the Elderly: An Australian Perspective

Abstract: Pharmacotherapy is an essential component of medical care for older patients, and around two-thirds of Australians over the age of 60 years use 4 or more drugs. Although polypharmacy is a well-known risk factor for adverse drug events, use of multiple drugs may be unavoidable in the elderly with multiple comorbidities. While there have been concerns about inappropriate prescribing, polypharmacy and non-adherence, it is now recognised that there are a broader range of drug-related problems that need to be addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 82 publications
5
113
2
3
Order By: Relevance
“…7 It was reported that approximately 70% of elderly women and 60% of elderly men take at least four medications (prescription and non-prescription) daily. 8 These statistics highlight the vulnerability of elderly patients to interruptions in continuity of care, and access to essential medications during a natural disaster. It is therefore imperative that healthcare policymakers develop adaptive, climate change-resilient, health care systems.…”
Section: Introductionmentioning
confidence: 99%
“…7 It was reported that approximately 70% of elderly women and 60% of elderly men take at least four medications (prescription and non-prescription) daily. 8 These statistics highlight the vulnerability of elderly patients to interruptions in continuity of care, and access to essential medications during a natural disaster. It is therefore imperative that healthcare policymakers develop adaptive, climate change-resilient, health care systems.…”
Section: Introductionmentioning
confidence: 99%
“…To treat these, many elderly people receive polypharmacy, with the attendant risk of drug/drug interactions that increases exponentially with the number of medications taken 83 . It has been shown that about two-thirds of communitydwelling people aged460 years take four or more medications daily, frail elderly people with multiple comorbidities take an average of nine 84 , and elderly hospital in-patients may be prescribed as many as fourteen 83 . The probability of interactions may be further increased by the consumption of over-the-counter (OTC) medications, which many patients perceive to be unimportant and do not disclose to their physician.…”
Section: Comorbidities and Polypharmacymentioning
confidence: 99%
“…Jenis obat-obatan yang sering mengalami polifarmasi (12 yang melebihi indikasi klinis, pengobatan yang mencakup Terjadinya efek samping merupakan salah satu bagian paling tidak satu obat yang tidak perlu, dan penggunaan DRP yang penting. Pada penelitian ini didapatkan 14% empirik 5 obat atau lebih (8).…”
Section: Diskusiunclassified